Prevalence of antibodies against Borrelia species in patients with unclassified uveitis in regions in which Lyme disease is endemic and nonendemic. - Kimura, K (1995)
We studied 93 patients with unclassified uveitis from two regions in Japan (Hokkaido and Kanagawa) to assess the contribution of Borrelia species to this condition. The seroprevalence of antibody to Borrelia species was higher in patients from Hokkaido than in those from Kanagawa. The unclassified uveitis of seropositive patients was probably a complication of Lyme borreliosis since (i) the antibody titers were as high as those in clinically diagnosed Lyme disease patients, (ii) healthy controls from Hokkaido showed low seroprevalence in contrast with unclassified uveitis patients from Hokkaido, and (iii) the reaction pattern of antibodies in sera from patients with unclassified uveitis was the same as that in patients with Lyme disease. This is the first report to reveal the high risk of Lyme borreliosis in patients with unclassified uveitis in regions endemic for Lyme disease. In case of unclassified uveitis as well as in cases of inflammatory disease of unknown origin, Lyme disease should be taken into consideration, especially in regions in which Lyme diseases is endemic, even if it is reported only in animals.